Menakar Liberalitas Pemikiran al-Tufi tentang Maslahah dalam Hukum Islam - Bahri, Syaiful (IAIN Kediri, 2015)
This paper attempts to discuss Najmuddin al-TufiÃ¢â‚¬â„¢s thought on maslahah, as well as see the extent of his liberal idea. In order to unravel this problem, the author conducted a literature review to examine al-TufiÃ¢â‚¬â„¢s work, Risalah fi RiÃ¢â‚¬â„¢ayah al-Maslahah. This study resulted in two conclusions. First, al-TufiÃ¢â‚¬â„¢s thought on maslahah is quite controversial because it is delivered with provocative words. Al-Tufi states that in case of conflict between nasÃ‚Â and masalahah, the precedence is maslahah using Takhsis and Tabyin mechanisms. Second, al-TufiÃ¢â‚¬â„¢s thought canÃ¢â‚¬â„¢t be put into the category of liberal thought. Since, although al-Tufi states the permissibility displacing the position of nasÃ‚Â with maslahah, the process must be carried out with the TakhsisÃ‚Â and Tabyin mechanisms which are already popular practiced in Islamic Legal thoughts.Keywords: Al-Tufi, Maslahah, RiÃ¢â‚¬â„¢ayah al-Maslahah